Teacher versus student-centered learning in higher education: Which model best promotes equity and inclusion in Ghana? - Akoto-Baako, H.; Jotham Prem, H.; Ndwandwe, N. D. (South African Journal of Higher Education, 2026)
This conceptual article explores the discourse of teacher-centred (TC) versus student-centred (SC) through the lenses of Freire’s critical pedagogy, Sen’s capability approach, and Vygotsky’s social constructivism to establish which model best promotes equity and inclusion in Ghanaian higher education. The narrative analysis shows that TC models offer structured delivery but perpetuate hierarchies, while SC approaches may encourage engagement but also require significant institutional support. As such, neither paradigm adequately addresses the challenges of equity and inclusion. Instead, this study proposes a hybrid pedagogical framework that combines (1) scaffolded content delivery, (2) culturally responsive SC adaptations, and (3) strategic digital integration. For effective implementation, the model requires systemic reforms, including teacher development programs and infrastructure investments. The proposed blended approach transcends the TC/SC binary to create an inclusive academic environment in which diverse learners can thrive. This research contributes to the pedagogical discourse in the Global South by offering a context-sensitive model for equitable higher education in resource-constrained settings.